2004
DOI: 10.1002/npr.20001
|View full text |Cite
|
Sign up to set email alerts
|

Marks & Spencer implements an ethical sourcing program for its global supply chain

Abstract: CORPORATE SOCIAL RESPONSIBILITY

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 0 publications
0
27
0
Order By: Relevance
“…Previous research found that there was issue of fraud supplier audits for Asian supply chain in the perspectives of factory managers, CSR experts and CSR managers (Welford & Frost, 2006). However these fraud supplier audits was not mentioned in previous case study researches of PSR activities which conducted in IKEA and Marks & Spencer (Andersen & Skjoett-Larsen, 2009;Johnson, 2004). This mixed result poses a research gap for further studies in PSR activities.…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…Previous research found that there was issue of fraud supplier audits for Asian supply chain in the perspectives of factory managers, CSR experts and CSR managers (Welford & Frost, 2006). However these fraud supplier audits was not mentioned in previous case study researches of PSR activities which conducted in IKEA and Marks & Spencer (Andersen & Skjoett-Larsen, 2009;Johnson, 2004). This mixed result poses a research gap for further studies in PSR activities.…”
Section: Introductionmentioning
confidence: 94%
“…Purchasing social responsibility activities may consist of supplier audit, supplier selection, supplier monitoring, contract signing, training and education, rewards and partnership with regards to suppliers' CSR. Different researchers may also call PSR activities in different terms such as social responsible purchasing (Maria, 2010), socially responsible buying practices (Maignan & McAlister, 2003), supplier measurement (Novak, 2004), sourcing initiatives or ethical sourcing programs (Johnson, 2004). There is lack of research to study PSR activities for individual countries in Asia region.…”
Section: Purchasing Social Responsibility (Psr) Activitiesmentioning
confidence: 99%
See 3 more Smart Citations